Isolation and physicochemical characterization of TEMPO-oxidized cellulose nanofibers from edamame husk (Glycine max L. Merrill) and their use in composite membranes - Asfira, Yuanita Nanda; Holilah; Prasetyoko, Didik; Faradilla, RH Fitri; Asranudin; Pratama, Agus Wedi; Abdul Hamid, Zuratul Ain; Piluharto, Bambang; Rani, Mohd Saiful Asmal; Ramdhani, Eka Putra; Suryanegara, Lisman; Norrrahim, Mohd Nor Faiz; et al. (Elsevier, 2026)
Cellulose nanofibers (CNF) were isolated from a novel source, edamame husks (Glycine max L. Merrill), and their physicochemical properties were comprehensively characterized. Cellulose was initially extracted via alkali treatment and bleaching (Crystallinity Index 61.47 %) before being subjected to TEMPO-mediated oxidation to introduce carboxyl groups and facilitate nano-fibrillation. The resulting CNF exhibited a high aspect ratio with an average diameter of 4.936 nm (at 45 min oxidation). Fourier Transform Infrared (FTIR) spectroscopy confirmed the effective removal of non-cellulosic components, while X-ray diffraction (XRD) analysis revealed a decrease in crystallinity to 45.68 % following oxidation, indicating structural modification of the cellulose framework. Thermogravimetric analysis (TGA) showed a reduction in thermal stability for CNF compared to the original cellulose, consistent with the introduction of functional groups and reduced fiber dimensions. To demonstrate the utility of the CNF as a functional biomaterial, composite membranes were fabricated with natural rubber latex (NRL). This modification successfully shifted the surface properties from hydrophilic (Water Contact Angle 61.5°) to hydrophobic (Water Contact Angle 125.5°). This study elucidates the chemical and structural properties of CNF derived from edamame husks, highlighting its potential as a promising sustainable nanomaterial for advanced applications.